EDUCATION IN THE EARLY CHILDHOOD TOWARDS ENERGY SAVING BEHAVIOUR - Upik Elok Endang Rasmani (Early Childhood Education and Development Journal, 2019)
The purpose of this study is to implement a culture of energy-saving behavior. It is based on the implementation of basic energy-saving values, including (1) the development of a green education curriculum through energy conservation teaching materials of Economical, Wise and Smart to Use Energy. Also, (2) it encourages energy-saving behaviours, such as turning off devices that use energy while not in use, including lamp and AC. This strategy needs to be practiced continuously with teachers’ help to inculcate positive habits in children. The study uses a comparative approach which is often meant to describe the profound relationship and the influence between two or more facts and the object properties examined. A comparative study is used to determine the cause of behavioral differences or individual status. This study involves a follow-up to the correlation research.